Bone level around dental implants adjacent to teeth and implants - Gómez-Guzmán, John Jairo (2022)
[Objective] This investigation seeks to determine the difference in bone level around implants adjacent to teeth and implants. [Methodology] This cross-sectional study included 17 patients with a total of 51 stable implants with a functional loading of at least 6 months. These implants were located next to natural teeth, other implants, or both. All implants and adjacent teeth were clinically examined, and periodontal and peri-implant parameters were recorded. A radiographic analysis was carried out to measure the bone level around implants in relation to the implant platform. Data were analyzed to detect differences between bone levels on the side of an implant next to a tooth compared to those on the side of an implant next to another implant. Statistical differences were considered significant when p≤0.05. [Results] The distance from the crestal bone on the coronal side of the implant platform to adjacent teeth or implants was approximately 1 mm. The bone level in zones adjacent to other implants was more apically located (2.9 ± 1.4 mm) than was the case for bone levels on sides adjacent to natural teeth (1.3 ± 0.07 mm) and the difference in these distances was statistically significant (p<0.05). Bivariate analysis showed that the bone level around implants was more likely to be coronal in relation to the implant platform on the side adjacent to a tooth than on the side adjacent to another implant (p=0.04). [Conclusions] The results indicate that the bone level of implants adjacent to natural teeth is maintained more coronal as compared to implants adjacent to other implants. This suggests a greater stability of implants when they are located near remaining natural teeth.